Effect of Triiodothyronine and Cortisol on Development, Growth and Survival Rate of Sand Goby (Oxyeleotris marmorata, Blkr.) Larvae - R.R Sri Pudji; S. Dewi; M. Zairin Junior (Jurnal Akuakultur Indonesia)
ABSTRACT